2021
DOI: 10.1039/d1nr04361g
|View full text |Cite
|
Sign up to set email alerts
|

TiN nanoparticles deposited onto a D-shaped fiber as an optical modulator for ultrafast photonics and temperature sensing

Abstract: Titanium nitride (TiN) with outstanding physical and chemical properties, has earned as much attention. However, few studies has been conducted on the ability of TiN in ultrafast photonics field. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A nonlinear model described in the SI was adopted to match the measured data in Figure 2d. 30 The modulation depth α s and nonsaturable loss α ns were 7.6 and 37.5% at 1.56 μm. Using the same method, the saturable absorption properties were also investigated at 1 (11.5 and 27.3%) and 2 μm (7.2 and 42.6%) as displayed in Figure 2c,e.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A nonlinear model described in the SI was adopted to match the measured data in Figure 2d. 30 The modulation depth α s and nonsaturable loss α ns were 7.6 and 37.5% at 1.56 μm. Using the same method, the saturable absorption properties were also investigated at 1 (11.5 and 27.3%) and 2 μm (7.2 and 42.6%) as displayed in Figure 2c,e.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The balanced twin-wall test system was built to present the nonlinear properties of the fabricated CNO film (Figure S2). A nonlinear model described in the SI was adopted to match the measured data in Figure d . The modulation depth α s and nonsaturable loss α ns were 7.6 and 37.5% at 1.56 μm.…”
Section: Resultsmentioning
confidence: 99%
“…363 4.1.2.5 Metal nitrides and metal phosphides. There are reports about the plasmonic metal nitrides and phosphides such as TiN, [364][365][366] InN, 367 and Cu 3Àx P nanostructured materials 368 as the SAs for applications in passively modelocked fiber lasers. For instance, Xian et al reported the passively mode-locked fiber laser centered at 1562 nm with pulsed duration down to 763 fs in EDFL by using the TiN nanoparticles as the SA in 2019 (Fig.…”
Section: Passively Mode-locked Fiber Lasersmentioning
confidence: 99%
“…364 The TiN nanoparticles were also applied as the SA for generation of passively mode-locked TDFL centered at around 2 mm. 366 Nanocomposite such as the Au nanocluster-modified TiN nanomaterial was also applied as the SA for generation of passively mode-locked laser pulses in EDFL. 369 In summary, the nanostructured materials have been widely used as SAs for generation of laser pulses in the passively modelocked fiber lasers due to their advantages such as broadband saturable absorption performance, ultrafast response, as well as facile preparation and integration.…”
Section: Passively Mode-locked Fiber Lasersmentioning
confidence: 99%
See 1 more Smart Citation